Life Satisfaction, Income and Personality - Eugenio Proto; Aldo Rustichini (Institute for the Study of Labor (IZA), 2015)
We use personality traits to better understand the relationship between income and life satisfaction. Personality traits mediate the effect of income on life satisfaction. The effect of neuroticism, which measures sensitivity to threat and punishment, is strong in both the British Household Panel Survey and the German Socioeconomic Panel. Neuroticism increases the usually observed concavity of the relationship: individuals with a higher neuroticism score enjoy extra income more than those with a lower score if they are poorer, and enjoy extra income less if they are richer. When the interaction between income and neuroticism is introduced, income does not have a significant effect on its own. To interpret the results, we present a simple model based on Prospect Theory, where we assume that: (i) life satisfaction is dependent on the gap between aspired and realized income, and this is modulated by neuroticism; and (ii) income increases in aspirations with a slope less than unity, so that the gap between aspired and realized income increases with aspirations. From the estimation of this model we argue that poorer individuals tend to over-shoot in their aspirations, while the rich tend to under-shoot. The estimation of the model also shows a substantial effect of traits on income.
Keywords: D03; D87; C33; 330; life satisfaction; income; personality traits; neuroticism; prospect theory